Women Rights Legal Awareness among Adolescents: Impact and Challenges A Preliminary Study - Rahi, Puneet Sohal; Bhatia, Ranjana (International Journal of Psychosocial Rehabilitation, 2020)
Adolescence is the age of several beginnings physical, psychological, social and emotional. It is the phase when the human body and mind evolves to lay the foundation of the adult one becomes in the coming years. Hence it becomes a significant part of one’s upbringing and life philosophy. This research was done on one such aspect of the adolescent’s awareness of women rights as provided by the Indian Constitution for the upliftment of Indian women. Considering the new Indian social structure, women are budding in their roles professionally and personally, but it has been observed that not all are aware of their rights. This research is centered on adolescents because when they become aware of women rights at an early age, they can be vigilant and productive adults who ensure judicious implementation of these rights. Random sampling method was used to draw the sample from the given population of adolescents of schools from New Delhi. Data was collected from 100 adolescents studying in government and private schools. The data was analysed through the triangulation of qualitative and quantitative techniques. The researcher analyses awareness about women rights as stated in the Indian constitution and how well the adolescents are informed about them. The paper investigates about the dimensions of legal awareness and draws inferences from the opinions shared by the adolescents about what new needs to be done in the education system for greater impact and dissemination of legal provisions and acts for the larger good of Indian social fabric.